Survival and Cause-Specific Mortality of Corsac and Red Foxes in Mongolia - Murdoch, J; Munkhzul, T; Buyandelger, S; Sillero-Zubiri, C (2010)
The corsac fox (Vulpes corsac) and red fox (Vulpes vulpes) range widely across northern and central Asia and may be declining in many regions due to overhunting and other causes. However, details of the fundamental causes of survival and mortality of both species remain largely unquantified, but may be crucial for understanding interspecific relationships and developing effective conservation actions. We studied a radiomarked population of sympatric corsac and red foxes in central Mongolia to quantify survival and cause-specific mortality rates from April 2005 to April 2007. Survival probability was 0.34 for corsacs (n=18) and 0.46 for red foxes (n=17) and did not vary by year within or between each species. Among both foxes, mortality occurred mainly from hunting by humans, but also from predation by larger canids and unknown causes. Our results suggest that illegal human hunting represents the principal source of mortality for both species and that a recently initiated ranger patrol program in the study area did not affect fox survival. As such, more stringent protective measures will likely be necessary to halt declines of both foxes. Our results also suggest that interference competition occurs between species as red foxes killed but did not consume corsacs. Our results will be useful for developing science-based management strategies to protect foxes in Mongolia, and in understanding the competitive relationships between them. © 2010 The Wildlife Society.